English medium instruction in emerging contexts: an editorial introduction to the special issue - Curle, S; Rose, H; Yuksel, D (Elsevier, 2024)
The burgeoning field of English Medium Instruction (EMI) has witnessed a significant increase in empirical studies yet remains largely insular and under-theorised. This special issue aims to address these gaps by spotlighting EMI in emerging contexts and interrogating its theoretical underpinnings. Comprising 10 empirical studies across diverse geographical and educational settings, this special issue, edited by Heath Rose, Samantha Curle, and Dogan Yuksel, offers a multifaceted examination of EMI's impact on language proficiency, academic achievement, and pedagogical practices. These studies contribute valuable insights into the complexities of implementing EMI. They also reveal a predominant focus on applied linguistics, often to the exclusion of other disciplinary perspectives. This editorial introduction critiques the current state of EMI research, calling for greater interdisciplinary collaboration and theorisation. It concludes with an urgent call for future research that is not only geographically diverse but also critically and theoretically robust. The overarching aim is to broaden the scope of EMI research, particularly in the face of the unrestricted Englishisation of global education systems.